2018
DOI: 10.31083/j.jmcm.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Re-assembled Casein Micelles for Oral Delivery of Chemotherapeutic Combinations to Overcome Multidrug Resistance in Gastric Cancer

Abstract: Multidrug resistance (MDR) mediated by ATP-dependent efflux transporters continues to be a dominant obstacle towards curative cancer therapy. We have previously demonstrated the ability of β-casein micelles (β-CM) to orally deliver a combination of individually encapsulated hydrophobic cargo of drugs and chemosensitizers designed to overcome MDR in gastric cancer. Herein we investigated the potential of reassembled casein micelles (rCM) to serve as a target-activated delivery platform comprising a synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…For this reason, casein is regarded as an excellent candidate as excipient for pharmaceutical applications in drug delivery. [20] Although other authors have previously reported the use of casein micelles (CM) as carriers for oral delivery of PTX in gastric carcinoma therapy [21][22][23][24][25][26], the parenteral application of this system in cancer therapy has not been reported in literature and could be of great interest for the pharmaceutical industry. CM are of particular importance due to their nanometric size in dispersion for intracellular drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, casein is regarded as an excellent candidate as excipient for pharmaceutical applications in drug delivery. [20] Although other authors have previously reported the use of casein micelles (CM) as carriers for oral delivery of PTX in gastric carcinoma therapy [21][22][23][24][25][26], the parenteral application of this system in cancer therapy has not been reported in literature and could be of great interest for the pharmaceutical industry. CM are of particular importance due to their nanometric size in dispersion for intracellular drug delivery.…”
Section: Introductionmentioning
confidence: 99%